Bebas Stunting sebagai Indikator Human Security Bagi Masyarakat di Provinsi Papua Barat Daya dalam Perspektif Hubungan Internasional - Melyana R. Pugu (Syntax Corporation, 2023)
This study aims to provide an analysis of the state of stunting in Sorong City, Papua Province. Stunting is a disease caused by lack of good nutritional intake for infant growth and development. Where babies with stunting conditions will have less or shorter height and are susceptible to disease. The fight against stunting has been waged worldwide spearheaded by the official international organization of the United Nations, the World Health Organization and approved in various international cooperation schemes including sustainable development schemes. This study uses qualitative research methods, namely research that describes and explains social phenomena with existing data and conditions to get answers to stunting conditions and stunting prevention in Sorong City. The results of this study found that the understanding of mothers and the number of facilities and infrastructure as well as medical personnel as well as a clean and healthy environment are the main factors in stunting prevention in Sorong City and the importance of the government's role to continue to protect citizens from the threat of stunting by providing nutrition and continuous socialization to the community so that the community is actively involved in handling stunting in Sorong City and the threat of stunting disease as a form of security threat Humans can be minimized and free from stunting conditions for a good future.